6,7-dimethoxydihydrocoumarin Compound from Ethyl Acetate Extracts from Steambarks Dysoxylum Alliaceum and Cytotoxic Activity Against P-388 - Ois Nurcahyanti; Kartika Rahma (Journal of Tropical Pharmacy and Chemistry, 2022)
Dysoxylum is a genus that has a variety of secondary metabolites. Research on various species of this genus is always growing and producing compounds that have interesting structures and activities, until now many compounds of the terpenoid group, chroman alkaloids, limonoids, sesquiterpenes, flavonoids, steroids, protolimonoids and sulfur have been reported. which is very interesting. One of the Dysoxylum species that has a variety of secondary metabolites is D. alliaceum. The purpose of this study was to obtain secondary metabolites of D. alliaceum bark. The bark of D. alliaceum was macerated successively with n-hexane, ethyl acetate and methanol. The ethyl acetate extract was separated and purified by various chromatographic techniques and was characterized using spectroscopic methods including, ultraviolet, infrared, NMR and mass spectroscopy and guided by thin layer chromatographic analysis to obtain the compound 6,7-dimethoxydyhidrocoumarin and the proposed biogenesis. The chemical structure of these compounds has been determined based on the interpretation of spectroscopic data and compared with spectral data from previous studies. Cytotoxic activity test against P-388 MTT leukemia cells obtained an IC50 of 39.210 g/mL and was declared inactive.